ASPEK KEUANGAN - Nur Habibah Angkat, Nur Habibah Angkat; Widya Ananda; Yulinda (Cahaya Ilmu Bangsa, 2024)
the aim of this research is to examine financial factors in relation to business financial management and how they influence financial performance. The main objective of this research is to determine the variables that influence the financial choices of a business and how these choices affect long-term growth and profitability. Using secondary data from the company's financial records for five years, a quantitative research methodology was used. The relationship between independent variables such as liquidity ratios, solvency ratios and profitability ratios with the company's financial performance was tested using linear regression techniques. According to research, profitability ratios are very important for improving long-term financial performance, while liquidity and solvency ratios have a big impact on business profitability. This study offers valuable information to stakeholders and financial managers to help them create better financial management plans. Keywords : Financial Aspects, Financial Ratios, Company Performance, Regression Analysis